Implementation of a force-resultant model describing spudcan load-displacement behaviour using an implicit integration scheme - Vlahos, G; Cassidy, M; Martin, C (2008)
This paper describes the numerical formulation of a force-resultant model describing the elasto-plastic load-displacement behaviour of a spudcan foundation in clay. The formulation uses an implicit integration scheme, which has the advantages of numerical efficiency and insensitivity to increment size. Importantly to the user, step-size does not require determination before investigating "unknown" problems. Implementation of the model as a user element subroutine for the commercially available finite element program ABAQUS is described. The formulation presented ensures optimum compatibility with the incremental-iterative solution scheme employed by ABAQUS itself, and therefore allows efficient integration with the range of structural elements available in ABAQUS. The implementation is verified against established analysis problems, including the pushover of a jack-up structure. Copyright © 2008 by The International Society of Offshore and Polar Engineers (ISOPE).